(3GdehWCs - (3eGdc Hf CfS Hf eGdc GdCUHMj GdMejQj, CHh YHO Gddg, J (B179 (3g` s
(3ChdgG (B:s
(3jHOC HHGH ehGbjJ GdUdGI s
(3BNQgG (B:s
(3eG OGeJ GdTeS HjVkG de JNGdWgG UaQg hgh bhd CHj MfjaI hGdYGeI ef efJgGfG Je GdcJGH GdeHGQc s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3JHUQI GdYfhGf (B:s
(3QhGjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B257 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B168s
Keywords: (3GdMOjK h GdeUWdMs